DINAMIKA KEBIJAKAN LAND CONVERSION DI KECAMATAN BUNGARAYA KABUPATEN SIAK - Fajar Alan Syahrier (LPPM Universitas Abdurrab, 2022)
This study wants to describe the dynamics of the Siak Regency Government's Policy in Overcoming the Transfer of Agricultural Land for Sustainable Food in Bungaraya District and the Factors influencing the Transfer of Sustainable Food Agricultural Land in Bungaraya District. The method used in this research is qualitative method. The theory that is used as the basis for the analysis is the theory of government policy, which includes the process of government functioning to control, serve, empower and regulate society. The results showed that the implementation of control carried out by the Siak Regency Government was to issue Regional Regulation No. 02 of 2014 concerning Protection of Agricultural Land to support sustainable food agriculture programs in Bungaraya District. The factors that influence the land use change policy in Bungaraya District include entrepreneur resistance, community economic factors and the political dynamics of government policies.